2003
DOI: 10.3166/ejc.9.190-206
|View full text |Cite
|
Sign up to set email alerts
|

State and Output Feedback Nonlinear Model Predictive Control: An Overview

Abstract: The purpose of this paper is twofold. In the first part we give a review on the current state of nonlinear model predictive control (NMPC). After a brief presentation of the basic principle of predictive control we outline some of the theoretical, computational, and implementational aspects of this control strategy. Most of the theoretical developments in the area of NMPC are based on the assumption that the full state is available for measurement, an assumption that does not hold in the typical practical case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
197
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(199 citation statements)
references
References 81 publications
0
197
0
2
Order By: Relevance
“…The fluorescence intensity of a single cell arbitrarily chosen at the start of the experiment, or the average fluorescence intensity of the cell population, was sent to a state estimator (extended Kalman filter discussed in SI Materials and Methods) connected to a model predictive controller (31). Model Predictive Control (MPC) is an efficient framework well-adapted Yeast cells grew as a monolayer in a microfluidic device that was used to rapidly change the cells' osmotic environment (blue frame) and image their response.…”
mentioning
confidence: 99%
“…The fluorescence intensity of a single cell arbitrarily chosen at the start of the experiment, or the average fluorescence intensity of the cell population, was sent to a state estimator (extended Kalman filter discussed in SI Materials and Methods) connected to a model predictive controller (31). Model Predictive Control (MPC) is an efficient framework well-adapted Yeast cells grew as a monolayer in a microfluidic device that was used to rapidly change the cells' osmotic environment (blue frame) and image their response.…”
mentioning
confidence: 99%
“…Similar sampled-data frameworks using continuous-time models and sampling the state of the plant at discrete instants of time were adopted in [4,7,8,6,16] and are becoming the accepted framework for continuous-time MPC. It can be shown that with this framework it is possible to address -and guarantee stability, and robustness of the resultant closed-loop system -a very large class of systems, which are possibly nonlinear, time-varying, and nonholonomic.…”
Section: Compute the Open-loop Optimal Controlū : [Tmentioning
confidence: 99%
“…In recent years, MPC has been applied over a wide range, from chemicals to transportation industries. 20,21) MPC is a form of control in which the controller output is obtained by solving an open-loop optimal control problem on-line at each sampling instant using the current state of the plant as the initial state. Optimization yields an optimal control sequence and the first control in this sequence is applied to the plant.…”
Section: Model Predictive Control Strategymentioning
confidence: 99%